Talking with adolescent and young adult cancer survivors about health after cancer: A review and communication guide for clinicians - Stephanie M. Smith; Lauren C. Heathcote; Jennifer N. John; Jasan Zimmerman; Catherine Benedict; Abby R. Rosenberg; Lidia Schapira (CA: A Cancer Journal for Clinicians, 2025)
Abstract Adolescent and young adult (AYA) cancer survivors represent a vulnerable population in cancer care and survivorship. AYA survivors are a heterogeneous group that includes people between the ages of 15 and 39 years who were treated for cancer during their childhood or AYA years, at which time they had variable agency and may have received cancer care in pediatric or adult settings. AYA survivors experience one or multiple health care transitions, moving from active oncology to posttreatment survivorship and/or from pediatric to adult care. Clinician communication that centers the needs and preferences of the AYA and their family (parent, partner, other support person) is a therapeutic tool that can support AYAs in these health care transitions and promote AYA engagement in their care. In this article, the authors review clinician communication practices through the lens of AYAs' and families' lived experiences with a focus on the initial diagnosis and treatment phase, completion of treatment, and throughout posttreatment survivorship care. Specific communication topics relevant to survivorship encompass managing uncertainty and fear of cancer recurrence, discussing treatment‐related future health risks, and supporting self‐management and engagement in care. Best practices for clinician communication include maintaining openness, compassion, and flexibility to re‐assess and adapt communication styles as an AYA cancer survivors' needs, concerns, and preferences change over time.